Involvement of phospholipase D in regulating expression of anti-microbial peptide human β-defensin-2 - Krisanaprakornkit S. (2014)
Human β-defensin expression correlates with differentiation in oral epithelium, and calcium ion, an important regulator of epithelial differentiation, plays a critical role in regulation of human β-defensin-2 (hBD-2) mRNA expression. Phospholipase D (PLD) also regulates epithelial differentiation. Therefore, we examined the role of PLD in hBD-2 up-regulation by cell wall extract of Fusobacterium nucleatum and phorbol 12-myristate 13-acetate (PMA), two known hBD-2 activators. We found that hBD-2 mRNA up-regulation in human gingival epithelial cells (HGECs) by these two activators was mediated by PLD activation and blocked by ethanol and 1-butanol, PLD inhibitors. PLD activity was induced by stimulation with these two activators, and phosphatidic acid (PA), a product generated from the PLD enzymatic activity, was detected in stimulated HGECs. Dioctanoyl PA commonly used for PA induced hBD-2 mRNA expression. mRNAs for PLD1α and β splice variants as well as PLD1 protein were constitutively expressed, whereas mRNA and protein for PLD2 were expressed at much lower levels than those for PLD1. Moreover, pre-treatment with (±)-propanolol, an inhibitor of phosphatidic acid phosphohydrolases that are the downstream signaling molecules in the PLD pathway, significantly blocked hBD-2 mRNA induction by PMA in a dose-dependent manner. In conclusion, these findings indicate the involvement of PLD activation in hBD-2 up-regulation in HGECs, which correlates with the state of epithelial differentiation. © The Japanese Society for Immunology. 2007. All rights reserved.